The Role of Reverse Shoulder Arthroplasty in Elderly Trauma: A Systematic Review - Dhaliwal, Kawaljit (Cureus, 2020)
Objectives: The primary objective of this systematic review was to evaluate pain relief and shoulder functional outcome following reverse shoulder arthroplasty for three- and four-part proximal humerus fractures in patients over the age of 60 years. The secondary objective was to assess the clinical end radiological complications following this procedure for this indication. Methods: Studies were identified using a MEDLINE search for relevant articles on 20th May 2019. The key terms ‘reverse shoulder arthroplasty’ and ‘proximal humerus fracture’ were used. Results: Five retrospective case-series fully met the eligibility criteria. No randomized controlled trials or meta-analyses were found. All of the studies agreed that reverse shoulder arthroplasty was able to offer good pain relief, function end range of forward flexion (FF), and abduction (Abd.). Restrictions in shoulder rotation have to be fully addressed. The rate of major complications, reduction in functional outcome, and development of scapular notching with time was a concern. Conclusions: Reverse shoulder arthroplasty for comminuted proximal humerus fractures has increased over the past several years, yet the published data evaluating the surgical outcome is limited. Large well-designed prospective randomized controlled trials are needed for comparing the various treatment options, in order to ensure that these patients receive the best treatment available.